Analysis of the Construction of the Meaning of Political Populism as Phenomenology in the Perspective of Civic Education - Randiawan Randiawan; Karim Suryadi; Prayoga Bestari (Universitas of Muhammadiyah Makassar, 2023)
Political populism is a phenomenon that can affect the health of democracy if misused by political actors, political populism is often only used as a strategy for political victory, so populism always has a negative meaning in society. The purpose of this research is to contribute in interpreting political populism from the perspective of civic education, it can describe the meaning of rational political populism in a democratic state through the dimensions of civic education as an educative process in society. This research uses a descriptive method with a qualitative approach. The results of this study describe political populism as something that can have a negative impact and can have a positive impact. So that through the study of civic education it is necessary to build the concept of rational populism. Rational populism is considered necessary in directing populism to have a positive impact on the development of democracy in Indonesia. Rational populism is a strategy in politics by prioritizing reasonable considerations, based on facts and data, and providing constructive narratives in the democratic process. Civics Education provides a more concrete and systematic picture and understanding of political populism. The conclusion of this research is that through the dimensions of civic education, namely, civic disposition and civic engagement as a lens in examining political populism as a more complex phenomenon, exploring the implications of political populism, thus providing a more comprehensive picture of its meaning. The meaning of political populism is a political strategy that can be built based on rational arguments supported by scientific facts and data.